2008
DOI: 10.1007/s11207-007-9079-2
|View full text |Cite
|
Sign up to set email alerts
|

Processing Method Effects on Solar Diameter Measurements: Use of Data Gathered by the Solar Disk Sextant

Abstract: To determine the apparent diameter of the Sun, it is first necessary to measure the shape of the intensity profile of the solar limb with an imaging optical system (hereafter denoted as a solar-limb profile). The inflection point of the limb profile is usually used as a reference for calculating the diameter. Because this point may be difficult to determine in the presence of noise, it is necessary to define an appropriate filtering process that eliminates noise while preserving the position of the inflection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 17 publications
(8 reference statements)
0
19
0
2
Order By: Relevance
“…Its one-dimensional version is applied to SDS data; more detail is given in Djafer et al (2008b). In the present work, we use the two-dimensional version of this method and apply it to the solar images acquired by the CCD astrolabe.…”
Section: Processing Methods Effectmentioning
confidence: 99%
See 3 more Smart Citations
“…Its one-dimensional version is applied to SDS data; more detail is given in Djafer et al (2008b). In the present work, we use the two-dimensional version of this method and apply it to the solar images acquired by the CCD astrolabe.…”
Section: Processing Methods Effectmentioning
confidence: 99%
“…For the FFTD method, the position of the inflection point is highly dependent on the value of the parameter a. The optimal value of a is 4 pixels (Djafer et al 2008b). For the solar astrolabe method, a window of 5 pixels is used.…”
Section: Processing Methods Effectmentioning
confidence: 99%
See 2 more Smart Citations
“…From recent accurate measurements taken with space telescopes, the oblateness amounts to about 8 mas (Emilio et al 2007(Emilio et al , 2009Fivian et al 2008;Kuhn et al 2012). It is found to be constant over the activity cycle by some authors (Kuhn et al 2012), but found to increase with decreasing activity by some others (Egidi et al 2006;Djafer et al 2008). …”
Section: Introductionmentioning
confidence: 96%